Scientific Approach to Enhance Scientific Literacy of Junior High School Students: Domain of Competence - Muhamad Gina Nugraha (Indonesian Journal of Educational Research and Technology, 2023)
Scientific literacy (LS) is the ability to engage with science-related issues, and with the ideas of science, as a reflective citizen. Thus, some developed countries provide policies, making that LS capabilities are provided to school curricula. However, some research reveals that this alleged ability has not been optimally provided in science learning, thus, students' LS abilities are still low. Pre-experimental research with a one-group pre-test-post-test design aims to get an overview of increasing LS capabilities in the competency domain through the application of a scientific approach. The study was conducted in one of the public schools in the city of Bandung using 30 samples taken randomly. The effectiveness of the increase was measured using the normalized gain value g on 20 essay questions with validity test results of 0.77, and reliability of 0.87. The results showed an increase in the K1 aspect (explaining scientific phenomena) g= 0.75 (high category), an increase in the K2 aspect (evaluating and designing scientific research) g= 0.46 (medium category), while an increase in the K3 aspect (interpreting data and evidence) g= 0.15 (low category). This shows the need for a mentorship process to build epistemic knowledge in analyzing and inferring experimental data in a scientific approach.